Health promotion and premarital education for Adolescents on Instagram @siapnikah_official - Lisnarini, Naurah; Setianti, Yanti; Ade muhtya Gobel, Sry; Febri Erlianti Safitri, Wafiq (Universitas Ahmad Dahlan, 2024)
Adolescent reproductive health and marriage readiness remains a significant issue in Indonesia, where one in nine girls marry before the age of 18, often with adverse health, social and educational impacts. To address these challenges, innovative approaches are needed, including the use of social media to provide easily accessible premarital education and health promotion. This research examines the role of the Instagram account @siapnikah_official in improving adolescent health literacy and preparing young individuals for marriage through digital engagement. This research aims to explore how @siapnikah_official provides premarital education, engages its audience, and promotes health awareness among teenagers. Using a qualitative descriptive methodology, this study collected data through in-depth interviews and content analysis of the account's posts, stories, and interactive features. The findings show that @siapnikah_official effectively uses Instagram features to disseminate important health information, encourage interactive learning, and promote positive behavior change. The use of visually appealing content, easy-to-understand stories, and active audience engagement strategies have contributed significantly to its success in addressing issues such as early marriage and reproductive health literacy. However, challenges remain, particularly in measuring audience acceptance and assessing the long-term impact of its health promotion efforts. This study underscores the potential of digital platforms as tools for strategic health communication and adolescent education. This study highlights the importance of integrating social media into public health initiatives to address pressing social issues, paving the way for further research on optimizing digital interventions for sustainable outcomes.